Antioxidant Activity Test Of Miana Leaf Ethanol Extract Using Dpph Method (1,1-Diphenyl-2-Picrylhydrazyl) - Aji, Nurwani Purnama; Noviyanty, Yuska; Rahmawati, Rahmawati (SINTA Journal (Science, Technology, and Agricultural), 2022)
The miana plant is an ornamental plant that has a purple color with a single leaf type, the purple color in the miana plant is an indicator of the presence of anthocyanin pigments which have antioxidant activity, with the activity possessed so that this plant can be used as a plant that can help overcome disorders in cells due to free radicals , so the purpose of this study was to determine the antioxidant activity contained in miana leaves (Coleus scutelleroides (L.) Benth).The sample in this study used miana leaves (Coleus scutelleroides (L.) Benth). The extraction method uses the maceration method with 96% ethanol and then evaporated with a rotary evaporator. Then the miana leaf extract was subjected to qualitative tests and continued quantitative tests in the form of antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazil) method by Uv-Vis spectrophotometry at a wavelength of 517 nm.The results of the qualitative test of the ethanol extract of miana leaves contain antioxidant compounds characterized by a change in color from purple to yellow and the quantitative test has the potential for antioxidant activity which is classified as strong, with an IC50 value of 54.39 Âµg/mL.